Bioflocs Technology: Theory and Application in Intensive Aquaculture System - Julie Ekasari (Jurnal Akuakultur Indonesia)
Bioflocs technology (BFT) is one of the developing technology in aquaculture which aimed to improve water quality and to enhance nutrient utilization efficiency. This technology is mainly based on the conversion of inorganic nitrogen in particular ammonia by heterotrophic bacteria into microbial biomass which further can be consumed by aquaculture organisms. The objective of this review is to discuss various aspect of BFT application in aquaculture including bioflocs formation process, technical requirement, bioflocs nutritional content and characterization techniques.